Impact of the Customers´ Behaviour Changes on Marketing Mix of the Banks in Slovakia - Jamborová , Erika Mária; Šprochová, Lenka (Asian Journal of Empirical Research, 2015)
In Slovakia as EU member country the crisis persists already eight years. This is reflected also in the changes of consumer behaviour. Banks have to react to the changed environment and adopt their marketing programs accordingly which also impacts satisfaction of their customer, consumers in banking sector. In retail banking the knowledge of the behaviour of local clients is very important for a bank. Therefore banks have to pay attention to the changes in purchasing behaviour of customers not only to achieve new clients, but also to build on the existing relationship with their customers to improve their competitiveness on the banking market. The aim of this paper is to point out the impact of the ongoing financial and economic crisis on changes in consumer behaviour in Slovakia in 2013 - 2014. Our research was conducted on a sample of Slovak consumers (for 2013 and 2014) in analysing changes in their behaviour and comparing them with the research conducted by Cetelem, which was based on an evaluation of 12 European countries including Slovakia for 2013 and 2014. The research observed verification of test hypothesis concerning the influence of crisis on consumer behaviour with possible impact to bank marketing strategy.